# Simplify the expression. Give the exact value in simplified form. Rationalize any denominator. 4 times the square root of 3 over 2 times the square root of 8

*print*Print*list*Cite

Student Comments

llltkl | Student

`(4*sqrt(3))/(2*sqrt(8))`

`=(4*sqrt(3))/(2*sqrt(4*2))`

`=(4*sqrt(3))/(4*sqrt(2))`

`=sqrt(3)/sqrt(2)`

Now, rationalising the denominator we get:

`=(sqrt(3)*sqrt(2))/(sqrt(2)*sqrt(2))`

Since, `root(n)(x)*root(n)(y)=root(n)(xy)` , we get:

`=sqrt(6)/2`

**This is the required answer.**